A grammar of Arabic - Brustad, Kristen (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"A Grammar of Arabic models a new framework for studying varieties of Arabic comparatively, highlighting the patterns of variation and consistency and showing how different styles, from primarily spoken and casual to primarily written and formal, are linguistically interrelated. This non-traditional reference grammar is structured around patterns of usage rather than prescriptive rules, aligning function with form and taking advantage of general principles of language. Using data from Classical Arabic, Arabic, Modern Standard Arabic, and dialects spoken in Morocco, Egypt, Sudan, the Levant, Iraq, and the Arabian Gulf, this grammar examines the actual usage of these language varieties, broadening understanding of Arabic dialects from a linguistics perspective whilst also giving readers the ability to engage language diversity. Designed for instructors, researchers and advanced students of Arabic, A Grammar of Arabic explores Arabic from an internally comparative perspective that will also be valuable to theoretical linguists"--
Phonology and orthography -- Roots, patterns and lexical innovation -- Inflection of nominals and verbs -- Nouns in context -- Verbs in context -- Basic sentence structures -- Interrogatives, conditionals, negation, and exception -- Sentence complements -- Mapping out physical and discursive location -- Linguistic tools of rhetoric.
Keywords: Arabic language -- Grammar; FOREIGN LANGUAGE STUDY / Arabic; LANGUAGE ARTS & DISCIPLINES / Grammar